A Look and Insight into Teacher Reflection - Majda Cencič, Majda Cencič (Sodobni didaktični diskurzi v kontekstu pedagoške tradicije: Monografija v počastitev 80-letnice prof. dr. Martina Kramarja, 2025)
This paper explores the concept of teacher reflection, examining it both narrowly and broadly, and considering it as a cognitive and affective process that should also incorporate an action-oriented dimension. We supplement this theoretical perspective with insights from practice, drawn from an unstructured interview with selected classroom teachers and responses to an online questionnaire completed by a small, non-random sample of teachers working in the first and second educational cycles. Based on the collected data, we summarize the approaches and tools most commonly used by teachers, how competent they feel in applying reflection, and the benefits they associate with reflective practice. We argue that it is crucial for teachers to be familiar with the concept of reflection and its benefits, and to have a positive attitude toward its implementation, despite often feeling overwhelmed by numerous responsibilities and lacking time for reflection. We further suggest that reflection should be promoted and developed with a stronger emphasis on its action-oriented dimension. Additionally, more attention should be given to reflection in teacher education programmes.